2020
DOI: 10.1371/journal.pcbi.1008543
|View full text |Cite
|
Sign up to set email alerts
|

PremPS: Predicting the impact of missense mutations on protein stability

Abstract: Computational methods that predict protein stability changes induced by missense mutations have made a lot of progress over the past decades. Most of the available methods however have very limited accuracy in predicting stabilizing mutations because existing experimental sets are dominated by mutations reducing protein stability. Moreover, few approaches could consistently perform well across different test cases. To address these issues, we developed a new computational method PremPS to more accurately evalu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
180
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(183 citation statements)
references
References 76 publications
3
180
0
Order By: Relevance
“…It has been shown that in vitro protein thermal stability and free energy of unfolding are correlated [23,34,35]. We therefore predicted the free energy of unfolding for CcdB mutants using SDM [36], mCSM [37], PoPMuSiC [38], DynaMut [39], DUET [40], MAESTROweb [41], DeepDDG [42], CUPSAT [43], PremPS [44] and INPS-MD [45]. We found moderate correlations, with DeepDDG performing the best (r=0.59), but still poorer compared to our prediction from YSD data (r=0.83).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that in vitro protein thermal stability and free energy of unfolding are correlated [23,34,35]. We therefore predicted the free energy of unfolding for CcdB mutants using SDM [36], mCSM [37], PoPMuSiC [38], DynaMut [39], DUET [40], MAESTROweb [41], DeepDDG [42], CUPSAT [43], PremPS [44] and INPS-MD [45]. We found moderate correlations, with DeepDDG performing the best (r=0.59), but still poorer compared to our prediction from YSD data (r=0.83).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the mechanistic basis for S54A selection, we analyzed the four FDA-approved mAbs listed above with this S54A mutation. To test for increased global stability of the mAbs, we utilized the online protein stability prediction algorithm PremPS (50) to determine the impact of reverting the alanine at position 54 in each of the four mAbs back to its identity of a serine in the respective germline sequences ( Figure 7B ). The A54S reversion mutation was predicted by PremPS to decrease mAb stability (calculated as ΔΔG) for all four mAbs, indicating the forward mutation (S54A) in the mature FDA-approved sequences was predicted to be stabilizing.…”
Section: Resultsmentioning
confidence: 99%
“…Full details of the modelling and ranking are shown in table 7. The effect of point mutations on the stability of the antigen candidates was assessed using PremPS, and the default criterion of (ΔΔG > 1 kcal mol -1 ) used to defining highly destabilising mutations (79).…”
Section: Methodsmentioning
confidence: 99%